A Suggested Model for Human Resource Governance in Arab Organizations - Ibrahim, Ahmed (The Arab Journal of Administration, 2022)
Human resources management governance is considered a new topic in the field of management studies in general and in the field of human resources management in particular. This study deals with reviewing aspects of corporate governance and human resources governance and aspects related to their application such as identifying stakeholders and the role of human resources in dealing with them and work ethics and social responsibility then It also deals with the bodies that set international standards for human resources governance. Accordingly, the study reached a proposed model for the application of human resources governance in the Arab countries as a framework for their application that can be guided by, especially in light of the lack of There are studies in this scientific field that need more future scientific research due to the lack of research in the Arabic language. In the end, the study reached some recommendations and proposals that may contribute to the application of human resources governance in the Arab countries in a way that reflects positively on human resource management practices in the Arab countries. This study is distinguished by being the first in the limits of the researcher’s knowledge after scanning the scientific field in this field in Arabic.